Efficacy and Safety of Mechanical Thrombectomy in Treating Acute Ischemic Stroke: A Meta Analysis. (3rd March 2016) - Liu, Yao; Zhang, Lin; Hong, Peiwei
ABSTRACT: Objectives: Mechanical thrombectomy (MT) is a promising treatment for acute ischemic stroke (AIS). But the results of completed trials were contradictory. Hence, we performed a meta-analysis to evaluate the efficacy and safety of MT in treating AIS. Methods: Literatures were searched in the databases including Pubmed, Cochrane Library, Web of Science and Ovid-SP. The bias and quality of publications with randomized controlled trials (RCTs) were assessed with the Cochrane collaboration's tool for assessing risk of bias. Results: Totally 16 publications matched the inclusion criteria, including seven independent RCTs and 2043 AIS patients. The results showed that the recanalization rate and the modified Rankin score of 0–2 at 90 days after treatment were better in MT combining standard care group, but the mortality had no significant difference, even the incidence of intracerebral hemorrhage during follow-up period was worse, as compared with standard care group. Conclusion: MT combining standard care would be an effective and promising treatment for AIS patients according to the present study.